Pengembangan Data Base Terdistribusi untuk Aplikasi Cloud Computing - Pitriyani, Selvisah; Firdaus, Rayyan (Universitas Pahlawan Tuanku Tambusai, 2024)
With an emphasis on capability analysis, this research investigates the integration of distributed databases in the context of Cloud Computing. The foundation of cloud-based information systems, Cloud Computing, has revolutionized the way businesses access and manage their data and applications. Data processing and storage on the internet network has taken over the role of local data processing and storage. In the context of Cloud Computing deployments, I examine the effects of performance, data security, and dynamic scalability in this analysis. Cloud Computing, Information is stored permanently on internet servers and temporarily on user (client) computers, including desktops, tablets, notebooks, wall computers, handheld devices, sensors, monitors, and more. This paradigm is known as cloud computing, and turns the internet into a data and application management center with users granted login privileges. Additionally, Cloud Computing is a way to hide complex infrastructure behind an abstraction. This computing method offers IT resources as a service, allowing anyone with an internet connection to access them without requiring in-depth knowledge of the content, technical expertise, or control over the underlying infrastructure. Thus, the performance analysis of the distributed Data Base. Understanding how these systems function in the demanding conditions of a dynamic and adaptable Cloud Computing environment becomes critical in this setting. Cloud Computing is a technology that can be used in a variety of industries, including government organizations, healthcare, education, and others. This technology has proven to be very useful in storing various types of data. Uses a computing model where data storage, networking, and software that functions across the network can be accessed at any time and from any location with an internet connection. Networks, servers, software and services are part of the easily controlled computer resources that can be shared among various users through the concept of Cloud computing. There is little managerial effort and service provider involvement required to organize and launch these resources.